István Bibó's Four-Point Solution to the Hungarian Problem: Translation of his Memorandum Published in German by the Viennese Newspaper "Die Presse" - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): István Bibó István Bibó, Minister of State in the Imre Nagy government and a former University Professor (in jail at the time of publishing of this memorandum), proposes a four-point solution that he believes expresses the wish of the Hungarian people and which presents a possible way out of the crisis and a democratic solution without hurting basic Soviet interests: 1) For the West not to drop the Hungarian question from its agenda. 2) For all countries of the Soviet bloc, the complete elimination of Stalinist political practices. 3) Accepting a "third way" of economic and political life that is a democratic form of socialism 4) Hungarian people have a duty to carry the flag of their revolution high, the flag of a free future for the whole of humanity.